Features Of The Manifestation Of The Phenomenon Of Intertextuality In The Aesthetics Of Postmodernism - Zakaryan, Hripsime (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
In 1967, the theorist of post-structuralism Yu. Kristeva, proposing the term intertextuality, argues that each text, along with its content and structural independence, in a hidden or unconcealed way, carries other textual elements. Indeed, modern literature is characterized by an intertextual character, a visible variety of interrelated texts, connected by many threads with cultural tradition. The article attempts to consider intertextuality with references to theoretical thought, on the one hand, as a form of manifestation of postmodern textology, a unique artistic invention, ultimately an integral part of postmodern poetics, on the other hand, as an aesthetic principle in general, the unique quality of a particular text, created in different historical epochs. Intertextuality is not limited to postmodern aesthetics, but the special nature of postmodern text creation and text perception allows us to interpret the nature of the term intertextuality in a different way. The main purpose of the article is, if possible, to trace the features of the manifestation of the phenomenon of intertextuality in a postmodern text, to identify whether intertextuality can be considered as a general artistic device or is it just a special quality of postmodern aesthetics. To achieve this goal, we set the following research objectives: within the framework of this article, subject to reasoned consideration possible theoretical concepts that characterize the essence of postmodern aesthetics, in this context, in a theoretical analysis, to determine the features of the manifestation of the term intertextuality in its various expressions, determine the role of the phenomenon of intertextuality in the process of postmodern text construction. The article is based on the theoretical basis of U. Eco, M. Epstein, R. Barthes, J. Baudrillard, J. Derrida study and others.